Research status and prospect of fault diagnosis technology for mine high voltage circuit breaker - Ali HUI; Qi QIN; Rui LI; Xiang RONG (Meikuang Anquan)
This paper introduces the basic situation of mechanical fault diagnosis technology for mining high voltage circuit breaker. According to the basic process of fault diagnosis, the current research status and main shortcomings of mechanical fault diagnosis technology of high voltage circuit breaker are summarized from four aspects: circuit breaker state characteristic signal, signal preprocessing, feature extraction and dimension reduction screening and fault diagnosis method. In view of the limitations of the current single signal, the occurrence of composite faults, the huge workload of establishing diagnostic models, and the problems of without considering data imbalance and unmarked fault data, the future research direction of fault diagnosis of high-voltage circuit breakers is prospected.